ADONIS Y LOS SEMIDIOSES. THEOC. 15.136-142 - Montes Cala, José Guillermo (Myrtia, 2000)
At lines 136-142 of Theocritus' Idyll XV Adonis is distinguished from other demigods because he is the only one to revisit alternately Earth and Hades; no other hero (not even the most celebrated) has been granted this. However, this catalogue has presented some textual and interpretative problems to the critics, who have insisted in describing it as clumsy and perfunctory. In this paper the author attempts to demonstrate that these lines, as composed and performed by the Argive woman's daughter, must be read in the light of heroic genealogy. She ascents from the Homeric age to the remotest antiquity in order to glorify Adonis as a new and prominent figure of the Ptolemaic pantheon.